(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
This work analyzes the economic feasibility of composting manure. The study looked beyond the field of literature data on a case study. The state of Santa Catarina stands out for volume production of pigs, being the first in the nation in pork production. Aiming to achieve the desired sustainability in the pig industry, it is necessary to develop alternatives that enable the system, both in terms of financial, economic and environmental. The treatment system of pig manure by composting process has the challenge to transform them from environmental liabilities in financial assets, environmental and even leave them in a position to generate income or still in use without environmental burden on the property itself. We present a case study of a composting project for a production unit piglet (UPL) with 950 pigs which rose the necessary investments, maintenance costs and production and also the prediction result which allowed the calculating the economic return on investment. Finally, it is concluded that composting of pig manure proves economically viable addition to the environmental benefits related to water resources, soil and atmosphere.